Determinants of CPAP Adherence in Hispanics with Obstructive Sleep Apnea. (5th February 2014) - Diaz-Abad, Montserrat; Chatila, Wissam; Lammi, Matthew R.; Swift, Irene; D'Alonzo, Gilbert E.; Krachman, Samuel L.
Abstract : Purpose . We hypothesized that socioeconomic factors and a language barrier would impact adherence with continuous positive airway pressure (CPAP) among Hispanics with obstructive sleep apnea (OSA). Methods . Patients with OSA who were prescribed CPAP for at least 1 year and completed a questionnaire evaluating demographic data, socioeconomic status, and CPAP knowledge and adherence participated in the study. Results . Seventy-nine patients (26 males;53 ± 11 yrs; body mass index( BMI ) = 45 ± 9 kg/m 2 ) with apnea-hypopnea index (AHI)33 ± 30 events/hr completed the study. Included were 25 Hispanics, 39 African Americans, and 15 Caucasians, with no difference in age, AHI, CPAP use, or BMI between the groups. While there was a difference in educational level (P = 0.006 ), income level (P < 0.001 ), and employment status (P = 0.03 ) between the groups, these did not influence CPAP adherence. Instead, overall improvement in quality of life and health status and perceived benefit from CPAP influenced adherence, both for the group as a whole (P = 0.03, P = 0.004, andP = 0.001, resp.), as well as in Hispanics (P = 0.02, P = 0.02, P = 0.03, resp.). Conclusion . In Hispanic patients with OSA, perceived benefit with therapy, rather than socioeconomic status or a language barrier, appears to be the most important factor in determining CPAP adherence.